2007
DOI: 10.1111/j.1462-5822.2006.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Early trafficking events of Mycobacterium ulcerans within Naucoris cimicoides

Abstract: SummaryThe severe skin-destructive disease caused by Mycobacterium ulcerans, named Buruli ulcer, is the third most important mycobacterial disease in humans after tuberculosis and leprosy. Recently we demonstrated that M. ulcerans could colonize the salivary glands of the water bug, Naucoris cimicoides. In this study, we report that M. ulcerans may be delivered from the digested prey aspirate to the coelomic cavity via a unique headspace, the head capsule (HC). During the infected meal, we observed that M. ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
1
30
0
2
Order By: Relevance
“…Genetic analysis indicates the emergence of M. ulcerans from M. marinum, a fish pathogen which can also cause disease in humans (Boddinghaus et al, 1990;Tonjum et al, 1998). There is a strong association between the occurrence of M. ulcerans infection in humans and slow-flowing or stagnant water bodies (Marsollier et al, 2007;Portaels et al, 1999;Roberts & Hirst, 1997;Ross et al, 1997;Stinear et al, 2000a). Aquatic snails (Marsollier et al, 2004), fish (Eddyani et al, 2004) and water bugs (Marsollier et al, 2002) are currently being discussed as passive and active hosts, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis indicates the emergence of M. ulcerans from M. marinum, a fish pathogen which can also cause disease in humans (Boddinghaus et al, 1990;Tonjum et al, 1998). There is a strong association between the occurrence of M. ulcerans infection in humans and slow-flowing or stagnant water bodies (Marsollier et al, 2007;Portaels et al, 1999;Roberts & Hirst, 1997;Ross et al, 1997;Stinear et al, 2000a). Aquatic snails (Marsollier et al, 2004), fish (Eddyani et al, 2004) and water bugs (Marsollier et al, 2002) are currently being discussed as passive and active hosts, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…When more discriminatory methods based on detection of variable number tandem repeats were used, many IS2404-positive environmental samples were reported to lack M. ulcerans (18). In light of these recent fi ndings, the relative frequency or abundance of M. ulcerans among aquatic invertebrates or other environmental reservoirs, remains tenuous, and thus, the role of aquatic insect vectors is uncertain.A series of laboratory experiments provided initial evidence for biting hemipteran vectors of M. ulcerans (19)(20)(21)(22)(23). Marsollier et al (9,24) demonstrated that a South American isolate of M. ulcerans could survive and multiply within the salivary glands of aquatic bugs indigenous to France (Naucoridae: Naucoris cimicoides).…”
mentioning
confidence: 99%
“…A series of laboratory experiments provided initial evidence for biting hemipteran vectors of M. ulcerans (19)(20)(21)(22)(23). Marsollier et al (9,24) demonstrated that a South American isolate of M. ulcerans could survive and multiply within the salivary glands of aquatic bugs indigenous to France (Naucoridae: Naucoris cimicoides).…”
mentioning
confidence: 99%
“…[7]. Une étude histologique a montré une localisation prépondérante sinon exclusive du bacille dans les glandes salivaires des punaises, et ce, paradoxalement, sans aucun dommage du parenchyme tissulaire malgré la capacité du bacille à produire une toxine cytotoxique [8,9]. Par ailleurs, nous avons rapporté que des plantes aquatiques servaient de support à la formation de biofilms [10,11] et pouvaient être à l'origine de la contamination transitoire de proies phytophages (mollusques) des punaises.…”
Section: éCologie Et Transmission De M Ulceransunclassified
“…La protection conférée aux souris par les piqûres d'insectes non infectés est associée à la production d'anticorps réagissant contre les protéines salivaires de naucoris, protéines qui entourent M. ulcerans pendant son séjour dans les glandes salivaires, et sont transmises avec le parasite lors de la piqûre. Ainsi, le parasite serait une cible « innocente » de cette réaction immune qui n'est pas dirigée directement contre lui [9]. Le même mécanisme protecteur surviendrait chez l'homme, puisqu'une analyse sérologique mesurant les immunoglobulines G reconnaissant des constituants du suc salivaire des punaises, réalisée en zone endémique, a montré chez les patients présentant des lésions à M. ulcerans un taux d'IgG infé-rieur à celui de sujets exposés aux piqû-res des insectes mais sans lésion [6].…”
Section: éCologie Et Transmission De M Ulceransunclassified